(untitled) (Modern education and development, 2025)
This thesis explores the significance of intellectual property rights (IPRs) under the World Trade Organization (WTO) legal framework and critically analyzes Uzbekistan’s current legal mechanisms in light of these international obligations. The research identifies gaps in domestic IP law, proposes tailored reforms, and emphasizes the legal, economic, and institutional importance of aligning national policies with the TRIPS Agreement. Using international comparative approaches and empirical data, the thesis offers a roadmap for enhancing legal coherence and fostering innovation.